Assessment of minimum ecological water requirements in Lake Pamvotida – Greece, using an adaptation of the IFIM method (Oral Presentation) - V. Chrysopolitou; E. Hadjicharalampous; E. Karadimou; D. Bousbouras; I. Leonardos; I. Kagalou; K. Chiotelli; Papadimos, D. (2025)
Oral Presentation in 13th World Congress of EWRA on Water Resources and Environment, Palermo, Italy 24 - 28 2025